2014
DOI: 10.1371/journal.pone.0097490
|View full text |Cite
|
Sign up to set email alerts
|

Severe Maternal Stress Exposure Due to Bereavement before, during and after Pregnancy and Risk of Overweight and Obesity in Young Adult Men: A Danish National Cohort Study

Abstract: BackgroundPerinatal stress may programme overweight and obesity. We examined whether maternal pre- and post-natal bereavement was associated with overweight and obesity in young men.MethodsA cohort study was conducted including 119,908 men born from 1976 to 1993 and examined for military service between 2006 and 2011. Among them, 4,813 conscripts were born to mothers bereaved by death of a close relative from 12 months preconception to birth of the child (exposed group). Median body mass index (BMI) and preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 34 publications
3
32
0
2
Order By: Relevance
“…It is noteworthy that our above-described finding on body composition is consistent with recent reports in large, national cohort samples linking pre-pregnancy and prenatal stress exposure related to maternal bereavement to risk of offspring overweight, obesity and risk for type-2 diabetes (Hohwu et al, 2014; Li et al., 2010; Virk et al, 2012), and our finding on immune function is consistent with another recent report linking prenatal maternal anxiety with infant illnesses and antibiotic use (Beijers et al, 2010). …”
Section: Prenatal Stress Exposure and Physical Health-related Outcsupporting
confidence: 92%
“…It is noteworthy that our above-described finding on body composition is consistent with recent reports in large, national cohort samples linking pre-pregnancy and prenatal stress exposure related to maternal bereavement to risk of offspring overweight, obesity and risk for type-2 diabetes (Hohwu et al, 2014; Li et al., 2010; Virk et al, 2012), and our finding on immune function is consistent with another recent report linking prenatal maternal anxiety with infant illnesses and antibiotic use (Beijers et al, 2010). …”
Section: Prenatal Stress Exposure and Physical Health-related Outcsupporting
confidence: 92%
“…Childhood changes in BMI, such as the ones observed here, predict cardiovascular and pulmonary health in early adulthood (Ziyab et al, 2014) It is plausible that prenatal exposure to maternal stress signals has long-term implications for how offspring utilize and conserve energy, leading to a ‘thrifty’ phenotype associated with higher risk for obesity. Recent studies have concluded that prenatal exposure to maternal bereavement stress is associated with increased likelihood of becoming overweight as early as 10 years old (Li et al, 2010) as well as a two-fold risk of obesity at age 18 among men (Hohwü et al, 2014). The present findings indicate that fetal exposure to pCRH is a plausible mechanism underlying programming of obesity risk.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, exposure to famine during pregnancy can have long-range consequences on offspring's morbidities including cardiovascular, metabolic, and mental diseases (6)(7)(8). Psychic suffering of pregnant mothers has been associated with functional alteration in the offspring's hypothalamo-pituitaryadrenal (HPA) axis (9,10) that may pave the way for psychic vulnerabilities (11), obesity (12), diabetes (13), and cardiovascular diseases (14).…”
mentioning
confidence: 99%